Isometric lat pulldown predicts 1 repetition maximum pull up in young competitive swimmers - Forsyth, J. R.; Steele, J. R. (Journal of Australian Strength and Conditioning, 2019)
An isometric lat pulldown is a useful measure of upper body strength in young swimmers.